Design of Combined Sliding Mode Controller Back Stepping Using Genetic Algorithm - Atefeh Marvi Moghadam; Saeed Balochian (Journal of Engineering)
This research has tried to achieve a new robust controller with back stepping control and sliding mode control method. Also as we know, in all analytical controllers there are constant coefficients like the back stepping and sliding mode controllers, redesigning the Lyapunov and the feedback linearization, - and so forth. There are two major problems in their set: firstly, the adjustment is cumbersome and time-consuming. Secondly, assuming that these parameters can be adjusted to workability, a designer can never tell exactly what are the parameters chosen to be optimal. To resolve this problem, the numerical algorithm which is a genetic algorithm is used here and we have the optimal parameters of the proposed controller. That genetic algorithm (GA) has been used to solve difficult engineering problems that are complex and difficult to solve by conventional optimization methods, and at the end of this section, we apply a new robust controller on ball and beam system. Simulation results are expressed.